Periosteal Sleeve Avulsion Fracture of the Quadriceps Tendon - van Sambeeck, Jordy; Arendt, Elizabeth; Rud, Christopher; Macalena, Jeffrey A. (The Journal of Knee Surgery Reports, 2016)
Sleeve fractures at the superior pole of the patella have been previously described in the literature. We present the case of a 15-year-old girl who sustained a patellar sleeve avulsion of the quadriceps tendon 1 month following patellar dislocation without surgical treatment. Open repair of quadriceps tendon was performed with subsequent union. Arthrofibrosis of the knee was noted; two subsequent manipulations and adhesiolysis were performed. At 18-month postinjury, normal motion and strength were present. Special attention to postoperative recovery of range of motion is imperative for good clinical outcome after periosteal sleeve avulsion fractures of the patella.
Keywords: sleeve avulsion; sleeve; quadriceps; rupture